(untitled) (Revista Contexto & Saúde, 2020)
Objective: To evaluate the self-efficacy, quality of life, anxiety and depression in patients with colorectal cancer. Method: A cross-sectional study performed with stomates of a city in the State of Rio Grande do Sul / Brazil. The data collection was through a questionnaire containing socio-demographic conditions and quality of life scales, perceived general self-efficacy and hospital anxiety and depression. Results: Auto efficacy was satisfactory. The highest domain of quality of life was social relations and the smallest in the physical domain, but in all domains it was satisfactory. About 24% had anxiety and 20% depression. There was a significant positive correlation between self efficacy and quality of life. Anxiety and depression in separate and quality of life there was significant negative correlation, high anxiety and depression demonstrates low quality of life. The correlation of self efficacy and anxiety and depression were not significant, there is a relationship of independence between variables. Conclusion: The stomates presented good self efficacy; quality of life with higher average in the domain of social relations and intermediate means in the psychological, physical and environmental domains. As for anxiety and depression the scores were low, therefore satisfactory.